the effect of job satisfaction, organizational commitment and work stress on the turnover intention assumption of employees of pt. asiatrust technovima qualiti samarinda branch - Hermin Nainggolan (Enrichment : Journal of Management, 2021)
his study aims to determine the effect of job satisfaction, organizational commitment and job stress on the assumption of employee turnover intention of PT. Asiatrust Technovima Qualiti Samarinda branch works either partially or simultaneously. The sample of this research is 132 employees of PT. ATQ who are still actively working are selected using random sampling technique. The method used is quantitative method, data collection is carried out using primary data through direct questionnaires to respondents. Data were analyzed with validity and reliability tests, as well as multiple linear regression analysis, t test, f test and classical assumptions. The results showed that H1: job satisfaction (X1), organizational commitment (X2), and job stress (X3) had a simultaneous effect on the assumption of turnover intention. H2: job satisfaction (X1) has a positive and significant effect. The results of this study also support previous research from Setiawan, et al. (2018) which states that job satisfaction (X1) has an effect on turnover intention (Y), and rejects the results of Saeka, et al. (2019) which states that job satisfaction (X1) has no effect on turnover intention (Y). H3: organizational commitment (X2) has a positive and significant effect on the assumption of turnover intention (Y). The results of this study also support previous research from Kurniawati, et al (2018) which stated that organizational commitment (X2) had an effect on turnover intention (Y), and rejected the results of Saeka's research (2019) which stated that organizational commitment (X2) had no effect on turnover. intention (Y). H4: work stress (X3) has a positive and significant effect on the assumption of turnover intention (Y). This study also supports previous research from Saeka, et al. (2019) which states that work stress (X3) has a significant and significant effect on turnover intention (Y), and rejects the results of research by Kurniawati, et al. (2018) which states that work stress (X2) has no effect on turnover intention (Y).